TINJAUAN HUKUM MENGENAI BENTUK BADAN HUKUM LEMBAGA MANAJEMEN KOLEKTIF DI INDONESIA - Sujana Donandi S (Problematika Hukum, 2016)
The existing legislation does not yet give clear boundaries regarding the form of legal entity of Lembaga Manajemen Kolektif (LMK) in Indonesia. The legal certainty about the form of legal entitiy of LMK is important to be examined as the basis for government and society in running and supervising LMK. This research is conducted through a normative legal research method using statute approachment dan utilizing primary and secoundary resources. The discussion shows that LMK is divided into 2, The LMK and LMK Nasional. The form of legal entity that lawfully allowed to establish LMK is Association because it meets the terms and condition as it is governed by legislation of copyright that LMK must be a legal entity, non-profitable, and membership basis. On the other hand, LMK Nasional is a public legal entity made by government.